Closing the loop: sustainable approaches for managing and recovering food industry residues - Silva, Lethicya Lucas Pires da; Perrone, Shannon; Reis, Carolina Leandra Fantt de Sousa e; Souza, Tainá Francisca Cordeiro de; Oliveira, Tatianne Ferreira de; Pereira, Julião (Revista Principia, 2025)
Food waste management is an increasingly critical global issue, driven by the need to promote environmental sustainability, conserve resources, and mitigate global hunger. This study provides a theoretical analysis of the historical evolution of food waste management, examining its definition and international significance. Additionally, it critically evaluates the necessity of adopting sustainable approaches. The methodology involves a comprehensive literature review covering 2013 to 2023, utilizing keywords related to food waste, sustainability, and the circular economy. The databases consulted include Science Direct and MDPI. The findings indicate a shift from individual to institutional sources of food waste, highlighting the need for alternative management strategies. The environmental analysis underscores the negative impacts of conventional practices, while solutions such as food rescue, fermentation, and anaerobic digestion emerge as promising alternatives. Understanding consumer behavior is key, with smart labels introduced as potential tools to reduce food waste. The article also discusses the challenges and limitations of current food waste management practices, reinforcing the necessity of sustainable treatment methods. The study concludes by outlining future research directions, emphasizing the importance of understanding consumer behavior, investigating the potential of smart labels, and addressing existing knowledge gaps to foster a more sustainable and responsible approach to food consumption and waste management.